2023
DOI: 10.1002/ange.202219181
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dissolution Dynamic Nuclear Polarization of [15N3]Metronidazole: A Clinically Approved Antibiotic

Abstract: We report dissolution Dynamic Nuclear Polarization (d‐DNP) of [15N3]metronidazole ([15N3]MNZ) for the first time. Metronidazole is a clinically approved antibiotic, which can be potentially employed as a hypoxia‐sensing molecular probe using 15N hyperpolarized (HP) nucleus. The DNP process is very efficient for [15N3]MNZ with an exponential build‐up constant of 13.8 min using trityl radical. After dissolution and sample transfer to a nearby 4.7 T Magnetic Resonance Imaging scanner, HP [15N3]MNZ lasted remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…35−42 Indeed, computational studies revealed the feasibility of employing HP uniformly 15 Nlabeled metronidazole ([ 15 N 3 ]metronidazole) for hypoxia sensing applications. 43 Moreover, pilot 15 N d-DNP studies using HP [ 15 N 3 ]metronidazole revealed the feasibility of in vivo utilization of HP [ 15 N 3 ]metronidazole in healthy rats. 43 These developments make HP nitroimidazoles in general and HP [ 15 N 3 ]metronidazole in particular promising magnetic resonance sensors with diagnostic specificity to tumor hypoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35−42 Indeed, computational studies revealed the feasibility of employing HP uniformly 15 Nlabeled metronidazole ([ 15 N 3 ]metronidazole) for hypoxia sensing applications. 43 Moreover, pilot 15 N d-DNP studies using HP [ 15 N 3 ]metronidazole revealed the feasibility of in vivo utilization of HP [ 15 N 3 ]metronidazole in healthy rats. 43 These developments make HP nitroimidazoles in general and HP [ 15 N 3 ]metronidazole in particular promising magnetic resonance sensors with diagnostic specificity to tumor hypoxia.…”
mentioning
confidence: 99%
“…43 Moreover, pilot 15 N d-DNP studies using HP [ 15 N 3 ]metronidazole revealed the feasibility of in vivo utilization of HP [ 15 N 3 ]metronidazole in healthy rats. 43 These developments make HP nitroimidazoles in general and HP [ 15 N 3 ]metronidazole in particular promising magnetic resonance sensors with diagnostic specificity to tumor hypoxia. 33 It was shown previously that [ 15 N 3 ]metronidazole can be successfully hyperpolarized in deuterated methanol via SABRE-SHEATH with P 15N of ∼16% for the 15 NO 2 group.…”
mentioning
confidence: 99%